PENGEMBANGAN LATIHAN PASS-SHOOT BOLA BASKET MELALUI MEDIA AUDIO VISUAL PADA CLUB BOLA BASKET GOSWEET GONDANGLEGI MALANG - Firdausia Yunita Budianti; Supriyadi Supriyadi; Olivia Andiana (Jurnal Sport Science, 2017)
Abstract The purpose of this study was to develop pass- shoot training guide through audio visual media. The research of pass shoot training, refer to the development model (research and development) Borg dan Gall (1983:775). The expected product specification is a video about the technic of passing and shooting basketball is: 1)background research, 2) understanding of passing, 3)understanding of shooting, 4) video passing and shooting training contains 14 training model. Based on the test results obtained a percentage of 87.75% belong to the category of very valid and Large groups of test obtained a percentage of 87.54% classified as very valid category that basketball pass-shoot training guides audio visual media can be used.Keywords: development research, audio visual media, basketball, passshot training.